Answer: The required solution is x = 6, -6.
Step-by-step explanation: We are given to solve the following quadratic equation using square roots :
![x^2+5=41~~~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ez09d1xedkksuhw5t15vv0ogvzjoyer51j.png)
To solve a quadratic equation by square root method, we need to take x² term on one side and the constant term on the other. After that, the square root on both the sides are taken.
From equation (i), we have
![x^2+5=41\\\\\Rightarrow x^2=41-5\\\\ \Rightarrow x^2=36\\\\\Rightarrow x=\pm√(36)~~~~~~~~~~~~\textup{[taking square root on both the sides]}\\\\\Rightarrow x=\pm 6.](https://img.qammunity.org/2019/formulas/mathematics/middle-school/clnzdqerzuhe2xs83rddwu17q1jyd3vrve.png)
Thus, the required solution is x = 6, -6.